Association of television viewing with mental health and mild cognitive impairment in the elderly in three European countries, data from the MentDis_ICF65+ project. (March 2015) - Da Ronch, C.; Canuto, A.; Volkert, J.; Massarenti, S.; Weber, K.; Dehoust, M.C.; Nanni, M.G.; Andreas, S.; Sehner, S.; Schulz, H.; Härter, M.; Grassi, L.
Abstract: Background: Time spent watching TV by Europeans has been calculated to be 22.1 h per week on average and it has shown to be correlated with a series of physical and mental problems in adults. Very little research is available in population over 65. This study aimed at evaluating the association between TV viewing and mental disorders and cognitive performance, taking into account the general physical activity level and socio-demographic characteristics in Europe. Methods: Within the MentDis_ICF65+ study, a subsample of 1383 subjects aged 65–84 years were assessed by the Composite International Diagnostic Interview (CIDI65+) and the International Physical Activity Questionnaire (IPAQ) for physical activity evaluation. Time spent in watching TV was assessed through a self report instrument. Results: Forty-three per cent of the total sample watched TV for 5–7 days a week for 2 or more hours every day. Females, people who lived alone, older subjects and those with lower education significantly watched TV for a longer time. Stepwise multiple regression showed statistically significant inverse correlation between Mini-Mental State Examination scores and TV viewing time ( p  < 0.001). Apart from a negative association with Major Depressive Disorder, no particular associations were found between TV viewing and psychopathological diagnoses. Conclusions: Given the relationship of time spending watching TV with cognitive impairment, awareness should be raised about the possible negative effects of TV viewing on the elderly and programs to reduce TV viewing time should be set up. Highlights: There are no multi-country studies on the effects of TV on the elderly. Data from the multi-centric MentDis_ICF65+ project were used. 85.5% ( n  = 1175) of the sample watched TV for 5–7 days a week. We found an association between TV viewing and Mild Cognitive Impairment. No association was found between TV viewing and Mental Health.